2021
DOI: 10.1002/jia2.25729
|View full text |Cite
|
Sign up to set email alerts
|

A decade and beyond: learnings from HIV programming with underserved and marginalized key populations in Kenya

Abstract: Introduction Key populations (KP) continue to account for high HIV incidence globally. Still, prioritization of KP in the national HIV prevention response remains insufficient, leading to their suboptimal access to HIV programmes. This commentary aims to share Kenya’s challenges and successes in achieving 2020 global HIV targets and scaling up the KP programme in the last decade. Discussion The KP programme in Kenya has scaled up in the last decade with the inclusion of female sex workers (FSW), men who have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Our qualitative study takes place within Nairobi’s urban core with two SAPTA facilities where PEs provide outreach and harm reduction services to surrounding PWID communities. The SAPTA service region caters to roughly 5,000–11,000 PWID, most of whom buy, sell and trade drugs within “dens” that are located in outdoor public spaces [ 9 ]. To avoid contributing to community stigma, location names will not be provided.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our qualitative study takes place within Nairobi’s urban core with two SAPTA facilities where PEs provide outreach and harm reduction services to surrounding PWID communities. The SAPTA service region caters to roughly 5,000–11,000 PWID, most of whom buy, sell and trade drugs within “dens” that are located in outdoor public spaces [ 9 ]. To avoid contributing to community stigma, location names will not be provided.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, PWID living with HIV are more susceptible to acquiring HCV and experiencing HCV-related morbidity and mortality [ 8 ]. Kenya’s national HIV program scale-up for key populations has resulted in significant reductions in HIV incidence among PWID, but service gaps remain with 57% of PWID unaware of their HIV status, 68% of PWID diagnosed with HIV are on antiretroviral treatment (ART), and 64% of those on ART are virally suppressed [ 4 , 9 ]. With the release of direct acting antiretrovirals (DAAs), which are over 90% effective in treating HCV within other PWID settings, HCV elimination is achievable and has shown promising, cost-effective results when incorporated into existing harm reduction and HIV programs for PWID [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been decades of investments made in the prevention and control of tuberculosis (TB) and human immunodeficiency virus (HIV), the two infectious diseases of global importance. Several studies have confirmed that TB and HIV will continue to pose major challenges without the deployment of innovative prevention and treatment strategies for everyone who needs them (17)(18)(19)(20)(21). For countries like Ethiopia that are overwhelmed by the dual burden of the two diseases, advancing the diagnosis, care, and treatment programs are essential to meeting global targets such as the 2035 End TB Strategy and the 2030 end AIDS epidemic (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%